If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 2x = 6x + -8 Reorder the terms: 2x + 2y = 6x + -8 Reorder the terms: 2x + 2y = -8 + 6x Solving 2x + 2y = -8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 2x + -6x + 2y = -8 + 6x + -6x Combine like terms: 2x + -6x = -4x -4x + 2y = -8 + 6x + -6x Combine like terms: 6x + -6x = 0 -4x + 2y = -8 + 0 -4x + 2y = -8 Add '-2y' to each side of the equation. -4x + 2y + -2y = -8 + -2y Combine like terms: 2y + -2y = 0 -4x + 0 = -8 + -2y -4x = -8 + -2y Divide each side by '-4'. x = 2 + 0.5y Simplifying x = 2 + 0.5y
| -6(8-3k)=22+4k | | a+5b+a+8c= | | (5x-4)(7x-6)= | | (-1-6)/(8-1) | | -31+3m=-6-5(m+5) | | 1.8u-2.3=8.5 | | y-7=-1(x-4) | | 10000x-66=42+200x | | -8(v+2)+4v+6=6v+8 | | 8x^2+11= | | -7=-6t+15 | | 0.1(x-0.2)-(x+0.5)= | | 6x-28=24 | | (4x+3)(2x+7)= | | log(logx-1)=0 | | 5x-(2x+x)=x+(3x-5) | | 4+P*0.0381/12 | | 61y=10 | | -7f=2*-7+8 | | 7(6x-5)+15x= | | 2l+2(70)=800 | | -9/7=-2x-x | | x-6=x-9 | | (w-5)(w+5)= | | 8=-5t-2 | | 4=3x/4-2 | | -2/x | | -125/x=-21 | | 6(2x+3)=24 | | -6u-30=0 | | 3z^2-10z+3=0 | | 4t+12=0 |